Dependence and Population Ageing - William A. Jackson (Dependency to Enterprise, 1991)
Population ageing has often been summarised through rising old-age dependence ratios. Age is therefore perceived as a source of dependence, which supposedly causes economic problems. While these perceptions seem intuitive, they are open to query and may be misleading. The current chapter looks at how we define dependence, how it relates to ageing, and whether it should be regarded as bad for the economy.
Keywords: J11; J14; J26; 330; dependence; population ageing; capability; economic activity; unemployment